2004
DOI: 10.1111/j.1601-5223.1997.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of Oil Field Wastewater in Nigeria

Abstract: The general toxicity (root growth inhibition and malformation) and genotoxicity (induction of chromosome aberrations in root cells) of an oil field wastewater have been investigated by the Allium test. A series of 10 small bulbs of Allium cepa L. were cultivated in various concentrations of the wastewater, and after 48 h one root tip from each bulb was harvested and processed for cytological studies by the aceto-orcein squash technique. After 96 h, mean lengths of root bundles were obtained and the Effect Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 22 publications
6
82
2
8
Order By: Relevance
“…The effects of spices were based on microscopic and macroscopic evaluations which include abnormalities like stickiness, vagrant type, sticky chromosome, laggard binucleate etc. The present study provides evidence that the uncooked spice (curry, thyme, suya and pepper soup spice) and the cooked spice (curry, thyme and pepper soup spice) inhibits root growth and caused retardation which is in agreement to the findings of Odeigah et al (1997).…”
Section: Microbial Analysis and Identification Of Isolates From Suya supporting
confidence: 82%
See 1 more Smart Citation
“…The effects of spices were based on microscopic and macroscopic evaluations which include abnormalities like stickiness, vagrant type, sticky chromosome, laggard binucleate etc. The present study provides evidence that the uncooked spice (curry, thyme, suya and pepper soup spice) and the cooked spice (curry, thyme and pepper soup spice) inhibits root growth and caused retardation which is in agreement to the findings of Odeigah et al (1997).…”
Section: Microbial Analysis and Identification Of Isolates From Suya supporting
confidence: 82%
“…This conforms to the finding of Bakare et al (2003), who reported reduction in mitotic indices obtained in the treated root A. cepa with increase in concentration of neem extract. With increasing concentration and increasing toxicity, there was an inhibitory effect on cell division (Odeigah et al, 1997).…”
Section: Microbial Analysis and Identification Of Isolates From Suya mentioning
confidence: 99%
“…It was not observed any anomalies in 48 and 96 h at 30 g/L. C-metaphase, a possibly reversible effect, might occur due to disturbed microtubules by Lg-ext and could be induced aneuploidies (Fiskesjö, 1988;Shahin & El-Amodi, 1991;Odeigah et al, 1997). Polyploidy cells can occur due to the lack of fragmoplast that prevents the formation of the daughter cells (Vidakovivé-Cifrek et al, 2002;Fernandes et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Findings indicate that in spite of all the level of toxicity of produced water effluent, there is paucity of information on their real impact on the exposed ecology [24,27]. Produced water from oil and gas industries often is permitted to be discharged to the environment [2,28].…”
Section: Environmental Effects Of Produced Watermentioning
confidence: 99%